KONSEP PLURALISME AGAMA PERSPEKTIF ISLAM DAN HINDU - Aulia, Mila; Putri, Mardliyatun Nahdliyah; Laily, Ridya Nur (Fakultas Dharma Duta, 2023)
ABSTRACT The rise of the issue of religious pluralism occurs because of the emergence of various social problems sparked by elements who experience a crisis of religious understanding such as perpetrators of acts of terrorism, violence, crime, anarchism, to bloodshed both within the internal and inter-religious spheres. In this case, it is not only Muslims who are busy voicing peace with religious pluralism. Other religions such as Christianity, Hinduism and Buddhism also contribute to this pluralism in order to create conditions for a safe, peaceful and peaceful state. This study will further examine the differences in perspectives between Islam and Hinduism regarding religious diversity. The purpose of the study is to compare the concept of religious pluralism between the Islamic perspective through the Qur'an and the Hindu perspective in the Vedas. This study is a qualitative-based research with a literature approach. The data collection method used is a documentation technique, while the data analysis method is a descriptive-comparative approach. In general, the religious teachings contained in the verses of the Qur'an and the Vedic verses imply the concepts of religious pluralism and peace. Furthermore, there is a common thread about the triadic relationship of good human relations between the teachings of Islam and Hinduism which are summarized in Mu'amalah ma'a Allah, Mua'amalah ma'a al-Nas & Mu'amalah ma'a al-Bi'ah from an Islamic perspective. , and Tri Hita Karana & Tat Twam Asi from a Hindu perspective. Regardless of the differences as well as the basis of the arguments of each sect, interreligious dialogue is still needed to – at least – minimize conflicts and tensions between religious communities towards harmonization and peace between religious communities. Keywords: Pluralism; Islam; Hindu; Comparative; Peace. ABSTRAK Maraknya isu pluralisme beragama terjadi karena mencuatnya berbagai permasalahan sosial yang disulut oleh oknum-oknum yang mengalami krisis pemahaman keagamaan seperti pelaku tindakan terorisme, kekerasan, kejahatan, anarkhisme, sampai pertumpahan darah baik dalam lingkup internal maupun antar agama-agama. Dalam hal ini, tidak hanya kalangan Islam saja yang ramai menyuarakan perdamaian dengan pluralisme agama. Agama-agama lain seperti Kristen, Hindu dan Budha pun turut menyemarakkan pluralisme ini demi terciptanya kondisi kehidupan bernegara yang aman, damai dan tentram. Kajian ini akan mengkaji lebih jauh perbedaan perspektif antara Islam dan Hindu terkait keragaman beragama. Tujuan kajian yaitu untuk mengkomparasikan konsep pluralisme agama antara perspektif Islam melalui al-Qur’an dan perspektif Hindu dalam Weda. Kajian ini merupakan penelitian berbasis kualitatif dengan pendekatan kepustakan. Metode pengumpulan data yang digunakan adalah teknik dokumentasi, sedangkan metode analisis datanya melalui pendekatan deskriptif-komparatif. Secara umum, ajaran keagamaan yang termuat dalam ayat-ayat al-Qur’an dan sloka-sloka Weda menyiratkan konsep pluralisme agama dan perdamaian. Selanjutnya, terdapat benang merah tentang triadik hubungan baik manusia antara ajaran agama Islam dan Hindu yang dirangkum dalam Mu’amalah ma’a Allah, Mua’amalah ma’a al-Nas & Mu’amalah ma’a al-Bi’ah perspektif Islam, dan Tri Hita Karana & Tat Twam Asi perspektif Hindu. Terlepas dari berbagai perbedaan sekaligus landasan argumen dari masing-masing aliran, dialog antaragama tetap dibutuhkan untuk – setidaknya – meminimalisir terjadinya konflik dan ketegangan antara umat beragama menuju harmonisasi dan perdamaian antar umat beragama. Kata Kunci: Pluralisme; Islam; Hindu; Komparatif; Perdamaian.